PENGEMBANGAN MEDIA PEMBELAJARAN POCKET CARD TERHADAP MEMBACA MENULIS PERMULAAN TEMA 7 KELAS 2 SD - nurul annisa; sujarwo (PGSD UMN Al-Washliyah, 2023)
This development research aims to develop Pocket Card learning media for reading and writing the beginning of theme 7 which is suitable for learning. This research is a type of research and development using the ADDIE development model. In this study, researchers carried out the ADDIE development model only up to the development stage. The instrument used to collect data is a questionnaire or questionnaire containing aspects of the assessment with statement items with the